Design of TRUST, a non-interventional, multicenter, 3-year prospective study investigating an integrated patient management approach in patients with relapsing-remitting multiple sclerosis treated with natalizumab - Ziemssen, Tjalf; Gass, Achim (BMC neurology, 2016)
Background: Natalizumab provides rapid and high-efficacy control of multiple sclerosis disease activity with long-term stabilization. However, the benefits of the drug are countered by a risk of developing progressive multifocal leukoencephalopathy in patients infected with the John Cunningham Virus. Close monitoring is required in patients with increased progressive multifocal leukoencephalopathy risk receiving natalizumab in the long-term for an optimal benefit-risk evaluation. Standardized high-quality monitoring procedures may provide a superior basis for individual benefit and risk evaluation and thus improve treatment decisions. The non-interventional study TRUST was designed to capture natalizumab effectiveness under real-life conditions and to examine alternate approaches for clinical assessments, magnetic resonance imaging monitoring and use of biomarkers for progressive multifocal leukoencephalopathy risk stratification. Methods/Design: TRUST is a non-interventional, multicenter, prospective cohort study conducted at approximately 200 German neurological centers. The study is intended to enroll 1260 relapsing-remitting multiple sclerosis patients with ongoing natalizumab therapy for at least 12 months. Patients will be followed for a period of 3 years, irrespective of treatment changes after study start. Data on clinical, subclinical and patient-centric outcomes will be documented in order to compare the effectiveness of continuous versus discontinued natalizumab treatment. Furthermore, the type and frequency of clinical, magnetic resonance imaging and biomarker assessments, reasons for continuation or discontinuation of therapy and the safety profile of natalizumab will be collected to explore the impact of a systematic patient management approach and its potential impact on patient outcome. Specifically, the role of biomarkers, the use of expert opinions, the impact of high-frequency magnetic resonance imaging assessment for early progressive multifocal leukoencephalopathy detection and the role of additional radiological and clinical expert advice will be explored. Discussion: TRUST was initiated in spring 2014 and enrollment is anticipated to be completed by mid 2016. Annual interim analyses will deliver continuous information and transparency with regard to the patient cohorts and the completeness and quality of data as well as closely monitor any safety signals in the natalizumab-treated cohort. The study’s results may provide insights into opportunities to improve the benefit-risk assessment in clinical practice and support treatment decisions.